ANALYSIS OF THE EFFICIENCY OF BANKS IN BOSNIA AND HERZEGOVINA BASED ON DEA AND SFA METHODS - Paunović, Slađana; Kovačević, Dajana (Economic Review: Journal of Economics and Business, 2025)
This paper analyzes the efficiency of banks in Bosnia and Herzegovina in 2023 using Data Envelopment Analysis (DEA) and Stochastic Frontier methods (SFA). The aim of the research is to measure the efficiency of banks in generating income, using variables such as total assets, number of employees and operating expenses as inputs, and interest and non-interest income as outputs. The results show that both methods produce similar average efficiency indices throughout the observed period. However, the analysis of the ranks indicates inconsistency in the assessment of efficiency at the level of individual banks. This suggests that while these methods provide stable insights into the overall efficiency of the banking sector, they become inconsistent when applied to individual banks.